Etiologies of Male Infertility in Dr. Cipto Mangunkusumo Hospital, Jakarta - Doddy H. Seno (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To have description about the etiologies of male infertility in Dr. Cipto Mangunkusumo Hospital. Method: This was a retrospective study of 315 male infertility patients treated at the Urology Department Dr. Cipto Mangunkusumo Hospital from January 2009 to June 2011. Result: There were 78 patients excluded from the analysis due to incomplete or missing data. The available data consisted of 237 males, with a median age of 35 years old. The median duration of infertility was 4 years. Primary infertility was identified in 89.4% and secondary infertility in 10.6% of all cases. Semen analysis results were classified as normal 2.5%, aspermia 1.3%, azoospermia 41.4%, multiple abnormal parameters 38.0%, single abnormal parameter (oligozoospermia 7.6%, asthenozoospermia 6.8%, teratozoospermia 2.1%), and cryptozoospermia 0.4%. From 237 subjects, there were 39 men (15.9%) with multiple etiologies of male infertility. The most common etiology in this study was varicocele (48.5%). Other etiologies were idiopathic 27.8%, acquired factors 14.3%, obstruction 8.0%, congenital anomalies 6.3%, urogenital infection 2.5%, sexual factors 2.1%, endocrine disturbance 2.1%, no demonstrable cause 1.3%, and other abnormalities 0.8%. This study also found Y-chromosome microdeletions in 2.5% of subjects or 6/98 (6.1%) of azoospermic patients. Lifestyle factors associated with male infertility were smoking 31.6%, alcohol consumption 13.4%, hot-bathing 6.7%, and sauna 2.9%. Conclusion: There are numerous possible contributing factors of male infertility, and varicocele was the most commonly identified etiology in this study. Some of our patients were presented very late for infertility treatment, therefore prompting the necessity to increase general awareness of male infertility in the society. [Indones J Obstet Gynecol 2011; 35-3: 130-4] Keywords: azoospermia, varicocele, risk factor